EFFICIENCY ANALYSIS MARKETING RUBBER KELAM PERMAI PEOPLE IN DISTRICT SINTANG WEST KALIMANTAN - NUGROHO, HADI; SUYATNO, ADI; RADIAN, RADIAN (Jurnal Social Economic of Agriculture, 2016)
This study aims to determine the structure and performance of the market, the costs, margins, marketing advantage, the farmer's share and profit margin ratio on each channel rubber marketing people in order to know the level of marketing efficiency.Determining the location and number of samples penelitiandilakukan intentionally (purposive) in District Kelam Permai Sintang, West Kalimantan.The market structure in the village, district and county are oligopsony low concentrations, indicating that traders do not have the level of power in influencing pasar.Hasili This study shows:1. Farmers still use the channel 3 (three) on the type of lump bowl and channels 3 and 4 on the type of bamboo lump fraction farmers because farmers are still bound by the village and district collectors.2. I channel marketing and channel I lump bowl bamboo lump most efficient marketing.